Determinant Theory of Quadri-Partitioned Neutrosophic Fuzzy Matrices and its Application to Multi-Criteria Decision-Making Problems - M. Anandhkumar; S. Prathap; R. Ambrose Prabhu; P. Tharaniya; K. Thirumalai; B. Kanimozhi (Neutrosophic Sets and Systems)
We propose a refined method to compute the determinant of matrices with a higher number of rows and columns. Furthermore, an algorithm is developed to address decision-making problems based on QPNFMs. An illustrative example is provided to demonstrate the effectiveness of the proposed method.